Persuasive Communication: What Do Existing Literature Tells Us About Persuasive Communication Among Students? - Tatum Derin; Mutia Sari Nursafira; Ratih Saltri Yudar; Nofita Sari Gowasa; Budianto Hamuddin (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
In comparison to studies on the improvement of students’ motivation to learn in class, there is a lack of studies on the improvement of students’ ability to motivate others to learn in class by persuasion. Meanwhile, Education Department students who are future teachers are expected and evaluated on their ability to be persuasive. As a first step to address this gap, this present study aims to review the current literature on the persuasiveness of students. Specifically, this study proposed the research question “What do existing literature tells us about persuasive communication among students?” Using keyword-based search as a basis for the library research method, from 269,000 results from Google Scholar this qualitative study collected a total of 76 as raw data over 3 months from October to December 2019. With NVivo 12 software, this present study selected only the most relevant studies to the research question to be analyzed. Analysis on the remaining 16 studies indicated that research interest in persuasive communication among students is increasing during the last five years. Many of the students’ involved in such studies, however, are mainly English, Business, or English Business students. There is still room to explore and learn more about persuasive communication with other types of variable and demography.